2023
DOI: 10.5194/essd-2022-451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Past and future discharge and stream temperature at high spatial resolution in a large European basin (Loire basin, France)

Abstract: Abstract. This paper presents retrospective simulations and future projections of daily time series of discharge and stream temperature for 52 278 reaches over the Loire River basin (105 km2) in France, using a physical process-based thermal model coupled with a hydrological model. Retrospective simulations over the 1963–2019 are based on the Safran meteorological reanalysis over France. 21st century projections are based on a subset of the DRIAS2020 ensemble projection dataset, derived from the Euro Cordex da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Accurate estimations of future river water temperatures and their interconnection with discharges are of paramount importance, particularly during low water and warm periods of the year [36]. For example, in the Loire River basin, France, Seyedhashemi et al found strong evidence of basin-wide increases in water temperature due to rising air temperatures and decreasing streamflow [42]. They proposed that some of these effects of climate change could be alleviated through the restoration and maintenance of riparian forests.…”
Section: The Examination Of the Relationship Between The Mean Annual ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate estimations of future river water temperatures and their interconnection with discharges are of paramount importance, particularly during low water and warm periods of the year [36]. For example, in the Loire River basin, France, Seyedhashemi et al found strong evidence of basin-wide increases in water temperature due to rising air temperatures and decreasing streamflow [42]. They proposed that some of these effects of climate change could be alleviated through the restoration and maintenance of riparian forests.…”
Section: The Examination Of the Relationship Between The Mean Annual ...mentioning
confidence: 99%
“…These findings are crucial for guiding water resource management, protecting river eco-hydrological processes, and comprehending their impact on aquatic ecology. Restoring riparian vegetation and shading can mitigate future increases in river water temperature [6,41,42]. Perry et al suggest that this approach can alleviate the impacts of climate change on flood damage to human infrastructure, riparian biodiversity, ecosystem vulnerability, and changes in river discharge [43].…”
Section: Introductionmentioning
confidence: 99%